Community-based education: reflections on teacher education - Ramírez Iñiguez, Alma Arcelia (2017)
This article presents an analysis about teacher’s education possibilities regardingtheir professional context in elementary education. For this, a conceptual reviewabout relationship between education and community is explained. In this analysis,the educational processes’ characteristics from this perspective are highlighted, aswell as their implications. Subsequently, some guidelines about teacher’s education from this view are exposed and a systemic approach of education are presented taking into account educational factors inside and outside the school, as well as the teacher as an agent who learns permanently.